2017
DOI: 10.3889/oamjms.2017.185
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects Associated With Exposure to Anesthetic Gas Nitrous Oxide-N2O in Clinical Hospital – Shtip Personel

Abstract: AIM:To show certain health effects associated with acute and chronic exposure to nitrous oxide of staff of the Department of Anaesthesiology and Intensive Care at the Clinical Hospital in Shtip.METHODS:A transversal study was conducted, that include 43 health workers (23 – exposed and 20 - unexposed). Personal exposure to nitrous oxide for this group members was assessed through continuous measurement over 8 hours shift within breathing zone of the subjects involved, using handheld electrochemical instrument w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(18 reference statements)
1
9
0
1
Order By: Relevance
“…The literature suggests that N 2 O-related neurological disorders are generally associated with intensive and long-term use [ 20 ]. Our study found that the number of N 2 O balloons used per week was a significant factor associated with the increase in the TNSc point.…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that N 2 O-related neurological disorders are generally associated with intensive and long-term use [ 20 ]. Our study found that the number of N 2 O balloons used per week was a significant factor associated with the increase in the TNSc point.…”
Section: Discussionmentioning
confidence: 99%
“…Study 4 [ 35 ]. Title: “Health Effects Associated with Exposure to Anesthetic Gas Nitrous Oxide-N 2 O in Clinical Hospital-Shtip Personel”.…”
Section: Resultsmentioning
confidence: 99%
“…Avoided emissions of high carbon propellants 56 57 Dependent on product Low carbon inhalers. Favour propellant-free devices and better condition management 55 Less risk to healthcare staff from occupational exposure to gases 59 Less CO2 and ozone depletion impact from anaesthetics 36 Dependent on product Low carbon anaesthetics and replacing surgical N2O with medical air/O2 58 Stimulating growth in cleaner, more environmentally responsible suppliers creates employment, reduced pollution, and supports the wider determinants of health Some LMICs and specific companies are already decarbonising Accounting and valuing CO2 in procurement can reduce supply chain emissions and encourage wider change Potential to stimulate industry and governments to invest in sustainability and green growth 61 62 Geographical sourcing to favour lower carbon country of origin 60 Favour low CO2 suppliers Favour low CO2 products, packaging, and logistics Wider scale of uptake and impact from measures such as those identified above Wider understanding and appreciation among the public and policy makers of the need to factor carbon and environmental issues into public planning and investment, in healthcare and beyond Safeguarding the environmental determinants of health Visible standards, targets, and public reporting of progress in decarbonised healthcare Advocacy Health professional's engagement with national and regional professional and media networks, encouraging clear commitments with practical actions 37 38 Health providers' engagement with governments encouraging policy and financial incentives for carbon reduction 3 33 36 Direct emissions from healthcare operations (scope 1), together with electricity (scope 2), typically comprise just over a quarter of the carbon footprint of healthcare. Energy and fuel use are also major sources of air pollution.…”
Section: Improved Management Of Respiratory Conditionsmentioning
confidence: 99%